Calam̐cā: cikicā dhaṃgu byākarana - Sresthacharya, Iswaranand. (Sudhādebi, 1967)
Brief tract on Newari grammar and orthography.
At head of title: Śrī 5yā sarakāra śikshā mantrālaya vibhāgaṃ 2024-2027-28 takayānimtiṃ khugū nhaygū va cyāgū tagiṃyāta svīkr̥ta.
Brief tract on Newari grammar and orthography.
In Newari.
Keywords: Newari language / Grammar / fast / (OCoLC)fst01036967; Newari language / Orthography and spelling.; Newari language / Grammar.